Da Qin i Seres – zarys kontaktów Imperium Rzymskiego i cywilizacji chińskiej - Janik, Paweł (Studia Azjatystyczne, 2016)
The relationships between the Roman Empire and the Chinese Empire existed, although different sources seem to indicate that they had only an indirect nature. They took place both by land and by sea. These contacts began around the turn of the era and continued until the end of European antiquity. They were then continued by Byzantium. Although these relationships were intermediate, both the Chinese and the Romans knew about each other. However, this knowledge was very unclear, and overshadowed by mythic imagination. However, there is evidence that both empires tried to get closer, but this never occurred. This does not change the fact that Chinese silk reached the Roman Empire, and Roman products like coins and glass cups were imported into the Middle Kingdom.